2017
DOI: 10.5539/elt.v10n12p164
|View full text |Cite
|
Sign up to set email alerts
|

Elaborative Feedback to Enhance Online Second Language Reading Comprehension

Abstract: Many higher education students across the world are studying in situations where a high proportion of the academic materials they encounter are online reading texts written in their second language. While the online medium presents a number of challenges to L2 readers, it also enables the provision of a range of support mechanisms, such as instant feedback. This quasi-experimental study investigated the use of two types of feedback, elaborative and knowledge of response, and compares their effectiveness for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Because the difference between the comparison and experimental groups was large, equal variance was not assumed. Bown (2017) investigated "Elaborative Feedback to Enhance Online Second Language Reading Comprehension" in this regard. A quasi-experimental study was undertaken on 113 male Emirati L2 English students aged 20 to 26.…”
Section: The Post-test Scores Of the Experimental And Comparison Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the difference between the comparison and experimental groups was large, equal variance was not assumed. Bown (2017) investigated "Elaborative Feedback to Enhance Online Second Language Reading Comprehension" in this regard. A quasi-experimental study was undertaken on 113 male Emirati L2 English students aged 20 to 26.…”
Section: The Post-test Scores Of the Experimental And Comparison Groupsmentioning
confidence: 99%
“…Bown used 113 samples in an experiment on the role of "Elaborative Feedback to Enhance Online Second Language Reading Comprehension" (Bown, 2017). The results of a quasi-experiment with low-proficiency readers who received elaborative feedback revealed that those who received elaborative feedback outperformed those who did not.…”
Section: Introductionmentioning
confidence: 99%